Dietary characteristics of community-dwelling older adults with poor appetite: a cross-sectional analysis - Scheufele, Pia; Rappl, Anja; Visser, Marjolein; Kiesswetter, Eva; Volkert, Dorothee (Age and Ageing, 2024)
Rationale: Poor appetite is considered a key factor in the development of malnutrition, a link that can be explained by alterations in dietary intake. Given the limited data on dietary characteristics in community-dwelling older adults with poor appetite, the present study aimed to examine whether poor appetite is associated with lower nutrient intake and more unfavourable food choices. Methods: In 569 participants of the Longitudinal Aging Study Amsterdam aged ≥70 years appetite was assessed using the Simplified Nutritional Appetite Questionnaire and dichotomised into normal (>14) and poor (≤14). Intake of energy, 19 nutrients, 15 food groups, the Dutch Healthy Diet Index 2015 (DHD15) and Mediterranean Diet Score (MDS) were calculated from a food frequency questionnaire. Dietary differences between appetite groups were examined using Mann–Whitney U test and binary logistic regression adjusted for potential confounders. Results: Mean age was 78 ± 6 years and 52% were female. Appetite was poor in 12.5% of participants. Energy intake was 1951 (median; quartiles 1–3: 1,653–2,384) kcal/day with no difference between appetite groups. Poor appetite was associated with lower intake of protein (OR 0.948, 95%CI 0.922–0.973), folate (0.981, 0.973–0.989), zinc (0.619, 0.454–0.846), vegetables (0.988, 0.982–0.994) and lower scores of DHD15 (0.964, 0.945–0.983) and MDS (0.904, 0.850–0.961), as well as higher intake of carbohydrates (1.015, 1.006–1.023), and vitamins B2 (4.577, 1.650–12.694) and C (1.013, 1.005–1.021). Conclusions: Community-dwelling older adults with poor appetite showed poorer diet quality with a lower intake of protein, folate, zinc and vegetables, compared with those reporting normal appetite and should be advised accordingly.
CRIS-Team Scopus Importer:2024-05-24
Keywords: anorexia of ageing; diet quality; malnutrition; older adults; poor appetite